Zinc bioavailability in maize grains in response of phosphorous–zinc interaction. Issue 1 (12th November 2015) - Imran, Muhammad; Rehim, Abdur; Sarwar, Nadeem; Hussain, Saddam
Abstract: Phosphorous (P) and zinc (Zn) are plant nutrients that interact with each other in soil–plant systems. Such interactions may cause deficiency of one of the nutrients interacting with each other if interactions are antagonistic. In the present trial, a field experiment was conducted to investigate the interactive effect of Zn (0 and 16 kg ha −1 ) and P (0 and 60 kg ha −1 ) on growth, yield and grain Zn concentration of two maize ( Zea mays L.) genotypes, i.e ., Neelam (local) and DK‐6142 (hybrid). Growth and yield of both maize genotypes were increased by the application of Zn and P treatments compared with control, but Zn+P was more effective than their sole application. When compared to control, combined application of Zn+P increased grain Zn and P concentrations by 52% and 32%, respectively, averaged for the two genotypes. Single application of P decreased grain Zn concentration by 10% over control. Application of P and Zn particularly in combination decreased the grain [phytate] : [Zn] ratio and increased the estimated human Zn bioavailability in grains based on a trivariate model of Zn absorption in both maize genotypes. Conclusively, combined Zn+P application appeared more suitable for enhancing grain yield and agronomic Zn biofortification in maize grains. However, Zn fertilization aiming at increasing grain yield and grain Zn concentration should consider the genotypic variations and P rate.